Cephalometric features of skeletal Class I, II and III (A comparative study) - Saad S Gasgoos; Ne'am R Al - Saleem; Khawla M Awni (University of Mosul, College of Dentistry, 2007)
Aims: To identify the cephalometric features of three skeletal jaw relations (Class I, II and III). Materials and methods: one hundred thirty four students were selected aged 12-15 years from secondary schools in Mosul City, 45 with Class I normal occlusion as control, 44 with Class II malocclusion and 45 with Class III malocclusion, after taking the lateral cephalometric radiographs according to ANB angle. A 20 variables (12 angular and 8 linear) were used in this study to correlate these variables in the three skeletal Classes. Results: No significant sex differences were observed for the majority of angular and linear measurements for the three skeletal types. Anterior cranial base length (S-N) and saddle angle (NSAr) didn't show significant difference among the three skeletal Classes, the posterior cranial base (S-Ar) was shorter in Class III which indicate the anterior articulation of the mandible. The length of maxillary base (ANS-PNS) was longer in Class II than Class I and III which lead to maxillary prognathism. The body length of the mandible (Go- Pog),effective mandibular length (Ar-Gn) and lower anterior face height was significantly longer in Class III which lead to mandibular prognathism. The SNA angle was significantly smaller in Class III than in the others. SNB and SNPog angles were larger in Class III followed by Class I and then Class II. The gonial angle (Ar-Go- Me) was larger in Class III which acts to increase mandibular effective length. The (N-A-Pog) showed as convex in Class II and concave in Class III. (The U1-PP) angle was larger in Class II followed by Class I and then by Class III. The (L1-MP) angle in Class II and III was significantly smaller than in Class I. Conclusion: Most of the angular and linear measurements indicated that the skeletal differences between the Class I, Class II and Class III are concentrated with in the maxillary and mandibular bases in both the anteroposterior and vertical dimensions and their type of articulation. The dental measurements appear to be compensated with that of skeletal one. Also these variables showed no significant sex differences in the majority of their measurements